El aporte de la neuroeducación en las habilidades cognitivas en los niños de 4 a 5 años del Preescolar Carrizales (2018)
This undergraduate work was carried out in order to identify the contribution of neuroeducation in cognitive skills in children between 4 and 5 years of age, from the reed preschool. For this reason, for the development and execution of the present work, it was agreed to carry out a process of observation and intervention, from a qualitative investigation with ethnographic technique, which proposed to participate in the situation, to analyze and to observe, to enter scenario, to know the population and to gather information, being necessary the constant contact with the population undertaken. During the process, pedagogical-participatory interventions are carried out, oriented to the internalization on specific subjects: attention, perception and memory, detecting interactions, behaviors, rhythm of the children, in this case; How it learns, processes, records, conserves and evokes information, among other things. So that, from this knowledge, the results of the research on the impact of neuroeducation in their cognitive processes will be achieved, respecting the good faith, confidentiality and intimacy of the children and favoring their spirit as part of the Early childhood education